(untitled) (Journal of Dhaka Medical College, 2021)
Objective: To see the maternal and fetal outcome in covid positive hospitalized pregnant women. Method: It is an observational study done in Mugda Medical College Hospital. Duration was from 23 April, 2020 to 16 June, 2020 . Result : 32 hospitalisedcovid positive pregnant women were studied. 84.4% women were above 25 years and 78% were multigravid. 19% had fever on admission and 59% had H/O fever. 22% had respiratory distress ranging from mild to severe on admission. During the hospital stay 28.2% needed ICU. 57.9% women delivered before completion of 37 weeks, among them. 26.3% were before 34 weeks. 79% women had delivery by Cesarean section and 10.5% had hysterotomy. In this study maternal mortality was 21% and 31.6% was perinatal mortality. There was no vertical transmission to fetus. Conclusion: During thisstudy , it is found that pregnancy outcome was not good in covid positive pregnant women . For the infected mothers early medical supervision and availability of ICU in critical condition is needed for better pregnancy outcome. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 153-157